The art of investigative interviewing - Yeschke, Charles L.; Black, Inge Sebyan (Elsevier, 2014)
The Art of Investigative Interviewing, Third Edition can be used by anyone who is involved in investigative interviewing. It is a perfect combination of real, practical, and effective techniques, procedures, and actual cases. Learn key elements of investigative interviewing, such as human psychology, proper interview preparation, tactical concepts, controlling the interview environment, and evaluating the evidence obtained from the interview.